A Peep inside an Online Pre-Primary Classroom during COVID-19 Times: Some Reflections - Singal, Pooja (Voices of Teachers and Teacher Educators, 2021)
This article briefly discusses some examples from the pre-primary classroom of a private school which serve to highlight the many ways in which a system continues to carry forward the conventional ways of educating young minds as against learning from theory and research from across the globe.